PERAN KEMANDIRIAN DAN KECERDASAN EMOSIONAL TERHADAP PENYESUAIAN DIRI PADA SISWA ASRAMA TAHUN PERTAMA SMK KESEHATAN BALI MEDIKA DENPASAR - Wulandari, Ni Kadek; Rustika, I Made (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Personal Adjustment is a process which includes all the individual behavior and mental response in harmonize needs and demands in which it is derived from the inside of individual as well as from the environment. The ability in personal adjustment is needed to help the individual in facing many changes and demands from the environment. Personal adjustment is needed for first-year students in facing the school’s transition, especially for the students who proceed their education in a boarding school. Personal adjustment is affected by the ability in managing the emotion and mental readiness to solve a problem without a help from others. This research is aimed to explore the role of autonomy and emotional intelligence to the personal adjustment in the first-year boarding students. The subjects were 125 boarding students in grade X of SMK Kesehatan Bali Medika Denpasar. The instrument in the research were personal adjustment scale, autonomy scale and emotional intelligence scale. The results of multiple regression analysis showed the value of R=0,783 (p<0,05) and R2=0,613, which concluded that the personal adjustment and emotional intelligence conjunctly contributes as much as 61,3% to the personal adjustment in th first-year boarding students. Standardized beta coefficient of autonomy showed the value of 0,296 (p<0,05), which concluded that the autonomy contribute to the personal adjustment. Standardized beta coefficient of emotional intelligence showed the value of 0,541 (p<0,05), which concluded that the emotional intelligence contribute to the personal adjustment.Keywords: autonomy, emotional intelligence, personal adjustment, boarding students, first-year